Effect of different parameters on uncertainty during evaluation of strength of dissimilar metal weld: Einfluss verschiedener Parameter auf die Unsicherheit während der Evaluation von Spannungen in artfremdem Schweißgut. Issue 9 (14th September 2016) - Santosh, R.; Singh, P. K.; Das, G.; Korody, J.; Das, S. K.; Kumar, S.; Ghosh, M.
Abstract : In scanning electron microscope tensile testing was carried out to assess the mechanical properties and consequent failure characteristics of dissimilar weld consisting of low alloy steel and low nitrogen austenitic stainless steel. These transition joints find wide spread application in pressurized heavy water reactors. A number of premature failures have been reported in recent past during service exploitation of same joints. Thus, it becomes essential to identify the governing criteria resulting in such type of de‐generation. In present endeavour, two types of joints were considered; one weld was fabricated by buttering with 309L stainless steel and the other one was made by buttering with IN82 Ni base alloys. From experimentation, weld strength was evaluated along with uncertainty analysis. Effect of various contributing factors over uncertainty was discussed. It was quantitatively shown that microstructural characteristics influenced more dominantly than physical parameters to the uncertainty of joint efficiency.